The Relationship Between Diet and The Incidence of Hypertension at The Buduran Sidoarjo Health Center - Ningrum, Anissa Widya; Moch Bahrudin; Hariono (Global Ten Public Health and Nursing Journal, 2025)
Hypertension or high blood pressure is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg at two measurements with an interval of five minutes in a state of adequate rest / calm (Ministry of Health RI, 2020). The incidence of hypertension at the Buduran Sidoarjo Health Center ranks 3rd with the number of patients served, which is 51.2% around 27,638. So researchers are interested in researching the incidence of hypertension. Objective: to determine the relationship between diet and the incidence of hypertension. Method: Quantitative analytical researcher design by using a cross sectional approach and using the chi-square test. The number of respondents was 40. This research will be conducted in February – March 2023. Dietary measurement with questionnaires and blood pressure measurement using a spghymomanometer. Results: Some respondents had a poor or poor diet with the results of 23 people (57.5 %), and had blood pressure hypertension grade 1 with an average systolic of 140-159 mmHg and diastolic 90-99 mmHg with the results of 23 people (57.5%). Analysis: Analysis in this scientific paper using the chi-square correlation statistical test obtained the result p = 0.091. This means that p is less than 0.10, so there is a relationship between diet and the incidence of hypertension at the Buduran Sidoarjo Health Center. Discussion: The majority of patients with hypertension have a poor or poor diet, it is also caused by other factors such as the age of the majority of the elderly, the gender of the majority of men, the last education of the majority of junior high school, and the work of the majority of housewives.